BIAKAN METODE TETRAZOLIUM MICROPLATE ASSAY TERKAIT DAHAK PASIEN TERDUGA TUBERKULOSIS PARU - Rita Rachmayanti; Ida Parwati; Tiene Rostini; Sylvia Rachmayati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
The definitive diagnosis of pulmonary tuberculosis is the discovery of Mycobacterium tuberculosis from sputum culture, but theconventional culture methods using Ogawa media require between 3−10 weeks detection time. Therefore it is needed a prompt diagnostictools to shorten the detection time. Tetrazolium microplate assay (TEMA) that used tetrazolium bromide as a growth indicator also usemitochondrial dehydrogenate enzymes in the mitochondria of living M. tuberculosis may reduce yellow tetrazolium bromide into purpleformazan crystals. The aim of this study was to know the validity and speed of time detection of M. tuberculosis growth by analyzingit. This study was carried out from November 2012 up to February 2013, which obtained 105 subjects conducted in the Departmentof Clinical Pathology at Dr. Hasan Sadikin Hospital with a cross sectional study design. The subjects consisting of sputum sample frompatients who suspected pulmonary TB which is examined for culture of M. tuberculosis with TEMA method using Ogawa media. Statisticalanalysis was used a 2×2 table to test the validity and Mann Whitney test for the differences in growth detection time. The validity testof TEMA method got the sensitivity of 90.4% and specificity of 96.2%. The detection time of M. tuberculosis growth in TEMA methodswas found fastest in the third day while from the Ogawa media cultur was found on the 13th day with the M. tuberculosis growth mediausing TEMA methods detected in 12 days. While for those cultured on Ogawa’s media the mean duration is 22 days (p<0.001). Basedon this study, can be concluded the examination of M. tuberculosis culture from sputum patient suffer of pulmonary TB with with TEMAmethod has given high validity and faster in the time detection for the diagnosis of pulmonary TB.